2017
DOI: 10.1186/s13662-017-1434-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid control of Hopf bifurcation in a Lotka-Volterra predator-prey model with two delays

Abstract: In this paper, the Hopf bifurcation control for a Lotka-Volterra predator-prey model with two delays is studied by using a hybrid control strategy. By analyzing the associated characteristic equation, its local stability and the existence of Hopf bifurcation with respect to both delays are established. In addition, the onset of an inherent bifurcation is delayed. Based on the normal form theory and the center manifold theorem, explicit formulas are derived to determine the direction of Hopf bifurcation and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In the remainder of this section, by using the algorithms in [18] and using a similar calculation process to that in [10], we obtain the coefficients used in determining the direction of Hopf bifurcation and the stability of the bifurcation periodic solutions: …”
Section: Direction and Stability Of Hopf Bifurcationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remainder of this section, by using the algorithms in [18] and using a similar calculation process to that in [10], we obtain the coefficients used in determining the direction of Hopf bifurcation and the stability of the bifurcation periodic solutions: …”
Section: Direction and Stability Of Hopf Bifurcationmentioning
confidence: 99%
“…They discussed complete analysis of local and global dynamical behaviors of this model by Filippov qualitative theory. Peng et al [10] proposed a hybrid control strategy in a predator-prey model. Their numerical simulation results showed that the hybrid controller is efficient in controlling a Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the analysis method is very similar to Section 2; we will omit the local stability and Hopf bifurcation analysis of system (24). We obtain the corresponding critical value of time delay ( ) ( ) as…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The aim of bifurcation control is to design a controller to modify the bifurcation properties of a given nonlinear system, thereby achieving some desirable dynamical behaviors. From the control theory point of view, many effective control methods have been proposed, such as the state feedback control [15,16] and hybrid control strategy [17][18][19][20][21][22][23][24]. Especially, the hybrid control has also been widely used recently.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation